Strategic Brand Management: Building, Measuring, and Managing Brand Equity, Global Edition - Keller, Kevin Lane; Swaminathan, Vanitha (Pearson International Content, 2019)
For courses in brand management. Create profitable brand strategies by building, measuring, and managing brand equity Strategic Brand Management: Building, Measuring, and Managing Brand Equity looks at branding from the perspective of the consumer, and provides a framework that identifies, defines, and measures brand equity. Using insight from both academics and industry practitioners, the text draws on illustrative examples and case studies of brands marketed in the US and all over the world. New co-author and award-winning scholar Vanitha Swaminathan, joins Kevin Lane Keller on this exciting, new 5th Edition. This edition also features a greater focus on digital branding, so students are aware of the exciting new opportunities and daunting challenges brands must face in connecting with today's consumers. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.